How Can Technology and Media Help in Improving Mental Health - Malini Deavi A/P Saravanan (IC-ITECHS, 2020)
Mental health is a topic that is often brought to surface this day and age. It is extremely significant as it greatly affects one’s life. It is important that we do not only manage physical hygiene, but mental hygiene as well. Mobile applications are available for smartphones to help those suffering from different mental health conditions such as depression, schizophrenia, anxiety and many more. Such apps are well-designed to track someone’s mood, and other symptoms, depending on the condition and the application itself. Technology enables us to get help from a therapist at the comfort of our own homes, through online platforms such as Google Meet. Technology of Virtual Reality for certain mental conditions such Post Traumatic Stress Disorder or PTSD can be used. This works by recreating similar situations that bothers the patient, and the continuous exposure will make the memory permanently lose its ability to trigger extreme emotional reactions towards said exposure. It is important to note that one’s experience on social media depends on how you choose to use, so for example, the kinds of accounts you decide to follow. Social media is an ideal platform to find new friends who share similar interests with and how this helps, is that more social connection helps the mind ease stress and strive for the better. Therapists can also utilize social media to promote their services, since it is a more relevant platform these days and will be able to reach a larger demographics of people. In retrospect, technology is significantly useful when it comes to mental health and conditions.